The relationship between physical activity and diabetes in middle-aged and elderly people - Tian, Ying; Li, Cheng; Shilko, Tatiana Alexandrovna; Sosunovsky, Vadim Sergeevich; Zhang, Yaqun (Medicine)
To investigate the association between diabetes symptoms and physical activity (PA) levels among middle-aged and older Chinese adults. Data for this study were obtained from 2018 Charles data. Ztest, logistic regression analysis, and linear hierarchical regression analysis were performed in 5352 individuals aged ≥50 years with complete information. In terms of diabetes, 6.8% of the middle-aged and elderly people with diabetes were detected, and 93.2% of the middle-aged and elderly people without diabetes symptoms. The proportion of middle-aged and elderly people with high PA levels was 50.5%, and the proportion of middle-aged and elderly people with low PA was 49.5%. There was a significant positive correlation between low PA and diabetes (P< .05). After adjusting demographic characteristics (gender, registered permanent residence type, education level, age, widowhood) and health status characteristics (poor mood, asthma, hyperlipidemia, disability, memory disease, self-assessment of health status, hypertension, smoking, stroke, depression), there was still a statistical significance between PA level and diabetes (P< .05). The risk of diabetes of middle-aged and elderly people in China increases with age, while the risk of diabetes of middle-aged and elderly people with low level of PA is higher. The risk of diabetes is high among middle-aged and elderly people who are old, have poor self-evaluation health, suffer from hyperlipidemia, memory disease, and asthma. The middle-aged and old people should increase their PA levels to prevent and improve diabetes.